Five years follow-up of implant-prosthetic rehabilitation on a patient after mandibular ameloblastoma removal and ridge reconstruction by fibula graft and bone distraction - Giacomo Oteri; Francesco Saverio De Ponte; Michele Pisano; Marco Cicciù (Wolters Kluwer Medknow Publications, 2012)
This case report presents a combination of surgical and prosthetic solutions applied to a case of oral implant rehabilitation in post-oncologic reconstructed mandible. Bone resection due to surgical treatment of large mandibular neoplasm can cause long-span defects. Currently, mandibular fibula free flap graft is widely considered as a reliable technique for restoring this kind of defect. It restores the continuity of removed segment and re-establishes the contour of the lower jaw. However, the limited height of grafted fibula does not allow the insertion of regular length implants, therefore favouring vertical distraction osteogenesis as an important treatment choice. This report presents a patient affected by extensive mandibular ameloblastoma who underwent surgical reconstruction by fibula free flap because of partial mandibular resection. Guided distraction osteoneogenesis technique was applied to grafted bone, in order to obtain adequate bone height and to realize a prosthetically guided placement of 8 fixtures. After osseointegration, the patient was rehabilitated with a full arch, screw-retained prosthetic restoration. At five-years follow up, excellent integration of grafted tissue, steady levels of bone around the fixtures and healthy peri-implant tissues were reported.